Updates on Hypoxia-Inducible Factor Prolyl Hydroxylase Inhibitors in the Treatment of Renal Anemia - Jing Li; Volker H. Haase; Chuan-Ming Hao (Karger Publishers, 2022)
Background: Anemia is a common complication of chronic kidney disease. The hypoxia-inducible factor prolyl hydroxylase inhibitor (HIF-PHI) is a new class of oral drugs for the treatment of renal anemia. Summary: Clinical trials have consistently shown that HIF-PHIs can effectively increase hemoglobin in both the dialysis population and the nondialysis population. The effects of HIF-PHIs in treating renal anemia include promoting endogenous erythropoietin production and facilitating iron mobilization. Several studies suggest that the erythropoiesis effect of roxadustat is less affected by inflammation. Careful monitoring of thromboembolic events and tumor before and during HIF-PHI treatment is necessary. Key Messages: HIF-PHIs are effective in correcting renal anemia. The long-term safety of HIF-PHIs needs to be further studied.